The Distribution of Effort : Physical Activity, Gender Roles, and Bargaining Power in an Agrarian Setting - Friedman, Jed; Gaddis, Isis; Kilic, Talip; Martuscelli, Antonio; Palacios-Lopez, Amparo; Zezza, Alberto (World Bank, Washington, DC, 2021)
The disutility of work, often summarily described as effort, is a primal component of economic models of worker and consumer behavior. However, empirical applications that measure effort, especially those that assess the distribution of effort across known populations, are historically scarce. This paper explores intra-household differences in physical activity in a rural agrarian setting. Physical activity is captured via wearable accelerometers that provide a proxy for physical effort expended per unit of time. In the study setting of agricultural households in Malawi, men devote significantly more time to sedentary activities than women (38 minutes per day), but also spend more time on moderate-to-vigorous activities (16 minutes). Using standardized energy expenditure as a summary measure for physical effort, women exert marginally higher levels of physical effort than men. However, gender differences in effort among married partners are strongly associated with intra-household differences in bargaining power, with significantly larger husband-wife effort gaps alongside larger differences in age and individual land ownership as well as whether the couple lives as part of a polygamous union. Physical activity -- a proxy for physical effort, an understudied dimension of wellbeing -- exhibits an unequal distribution across gender in this population.